PENGARUH PERTUMBUHAN EKONOMI DAN FORIGN DIRECT INVESTMENT TERHADAP DEGRADASI LINGKUNGAN DI ASEAN-5 - Febri Azka Dzikrullah; Deris Desmawan (Politeknik Bisnis Indonesia, 2023)
Environmental degradation and global warming are serious challenges occurring in the world today, and their damaging impacts are closely linked to economic activity. Along with rapid economic growth, human activities, such as industry, transportation, and agriculture, have increased greenhouse gas (GHG) emissions. The purpose of this study is to analyze the impact of Foreign Direct Investment (FDI) and economic growth on environmental degradation and test the existence of the Environmental Kuznets Curve (EKC) in five ASEAN countries namely Indonesia, Malaysia, Thailand, Philippines, and Vietnam in the period 2001 to 2019. In this study, panel regression was used for data analysis with the estimation model is Fixed Effect Cross-Section Weights. The results showed that economic growth has a significant positive effect on environmental degradation. FDI has a positive and significant effect on environmental degradation. Economic growth variable has a positive direction and GDP per capita squared has a negative direction on environmental degradation. This means that the Environmental Kuznets Curve Analysis applied in this study confirms the existence of an